T Cell Membrane Heterogeneity Aids Antigen Recognition and T Cell Activation - Farrell, Megan V.; Webster, Samantha; Gaus, Katharina; Goyette, Jesse (Frontiers in Cell and Developmental Biology, 2020)
T cells are critical for co-ordinating the immune response. T cells are activated when their surface T cell receptors (TCRs) engage cognate antigens in the form of peptide-major histocompatibility complexes (pMHC) presented on the surface of antigen presenting cells (APCs). Large changes in the contact interface between T cells and APCs occur over the course of tens of minutes from the initial contact to the formation of a large-scale junction between the two cells. The mature junction between a T cell and APC is known as the immunological synapse (IS), and this specialised plasma membrane structure is the major platform for TCR signalling. It has long been known that the complex organisation of signalling molecules at the IS is critical for appropriate activation of T cells, but within the last decade advances in microscopy have opened up investigation into the dynamics of T cell surface topology in the IS. From mechanisms mediating the initial contact between T cells and APCs to roles in the organisation of molecules in the mature IS, these studies have made it increasing clear that local membrane topology has a large impact on signalling processes. This review focuses on the functional consequences of the T cells’ highly dynamic and heterogeneous membrane, and in particular how membrane topology leads to the reorganisation of membrane proteins on the T cell surface.